2020
DOI: 10.1242/dev.193862
|View full text |Cite
|
Sign up to set email alerts
|

The conserved molting/circadian rhythm regulator NHR-23/NR1F1 serves as an essential co-regulator ofC. elegansspermatogenesis

Abstract: In sexually reproducing metazoans, spermatogenesis is the process by which uncommitted germ cells give rise to haploid sperm. Work in model systems has revealed mechanisms controlling commitment to the sperm fate, but how this fate is subsequently executed remains less clear. While studying the well-established role of the conserved nuclear hormone receptor transcription factor, NHR-23/NR1F1, in regulating C. elegans molting, we discovered NHR-23/NR1F1 is also constitutively expressed in developing 1° spermato… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
53
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 20 publications
(64 citation statements)
references
References 100 publications
(140 reference statements)
11
53
0
Order By: Relevance
“…Additionally, our sun-1p::TIR1::F2A::BFP::AID*::NLS transgene produced equivalent mNG::AID*::PAR-3 depletion and resultant synchronous cell division as compared to a sun-1p::TIR1::mRuby2 transgene ( Figure 2, C and D ). Similarly, using a mex-5p::TIR1::F2A::BFP::AID*::NLS transgene we observed complete sterility following NHR-23 or SPE-44 depletion, identical to that observed using pie-1p or sun-1p::TIR1::mRuby2 transgenes ( Kasimatis et al 2018 ; Ragle et al 2020 ). However, there may be cases where depletion rates affect phenotypic preference, so this point should be taken into consideration when choosing which TIR1 transgene to use.…”
Section: Discussionsupporting
confidence: 78%
See 2 more Smart Citations
“…Additionally, our sun-1p::TIR1::F2A::BFP::AID*::NLS transgene produced equivalent mNG::AID*::PAR-3 depletion and resultant synchronous cell division as compared to a sun-1p::TIR1::mRuby2 transgene ( Figure 2, C and D ). Similarly, using a mex-5p::TIR1::F2A::BFP::AID*::NLS transgene we observed complete sterility following NHR-23 or SPE-44 depletion, identical to that observed using pie-1p or sun-1p::TIR1::mRuby2 transgenes ( Kasimatis et al 2018 ; Ragle et al 2020 ). However, there may be cases where depletion rates affect phenotypic preference, so this point should be taken into consideration when choosing which TIR1 transgene to use.…”
Section: Discussionsupporting
confidence: 78%
“…AID*-tagged BFP is degraded in the presence of auxin, confirming TIR1 activity via degradation of an internal control ( Figures 2 and 3 , and Supplementary Figure S2 ). Recent work from our lab shows that our new TIR1 strains are effective for experiments where red FP imaging is desired ( Ragle et al 2020 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These results suggest a sexual dimorphic difference in auxin sensitivity in C. elegans , where male worms may absorb and process auxin differently than hermaphrodite worms. Although, recent study found that depletion of a different AID*-tagged protein (NHR-23) in the germline was equivalent between males and hermaphrodites on 4-mM auxin plates ( Ragle et al 2020 ). Thus, future studies focused on auxin processing in both C. elegans sexes may reveal the mechanisms behind this intriguing sexual dimorphism that may vary depending on the tissue assayed and AID*-tagged protein.…”
Section: Resultsmentioning
confidence: 99%
“…The specific knockdown of Rora in Sertoli cells at puberty leads to declined sperm count in rats ( Mandal et al, 2018 ). In C. elegans , NHR-23/NR1F1 (RORA) depletion causes infertility due to the arrest of primary spermatocytes rather than haploid sperm ( Ragle et al, 2020 ).…”
Section: Circadian Physiology In Major Organs Associated With Complex Diseasementioning
confidence: 99%